Evaluation of risk promoting effects for age-related macular degeneration by estradiol - Inga-Marie Pompös; Dietrich Polenz; Norbert Kociok; Silvia Winkler; Olaf Strauß (PLoS ONE, 2026)
Early menopause increases the risk for age-related macular degeneration (AMD), the most common cause of vision loss in industrialized countries. The supplementation with estradiol reduces the risk in these cases and suggesting that estradiol deficiency is a mediator of the risk association. We investigated rat models of estradiol deficiency mimicking either biological ageing (22 months of age) or early menopause by ovariectomy and age of 22 months. Serum analysis of gonadal hormones in both models showed the expected reduction in estradiol levels compared to 6 months old controls but also increases in progesterone, corticosterone and dehydroepiandrosterone sulfate (DHEA-S). Comparing the two estradiol deficiency models, we found no differences except for DHEA-S that were reduced in ovariectomized rats. The hormone status was associated with degenerative changes in the retina with higher activity of mononuclear phagocytes and p16/p21-dependent senescence. Mainly the estrogen receptor beta (ERβ) expressing cells were affected by estradiol deficiency: ganglion cells, cells of the inner nuclear layer (INL) and retinal pigment epithelial cells. An exception are photoreceptors that were ERβ negative, showed stronger degeneration in ovariectomized rats compared to sham treated animals. We conclude that either biological or ovariectomy induced estradiol deficiency might not cause but rather promote mechanisms that lead to AMD. The phenotype depends on a broader spectrum of altered hormones than on estradiol alone. Photoreceptor degeneration and cellular senescence that were ERβ independent in ovariectomized rats suggest non-estradiol effects to increase AMD risk by early menopause.